(untitled) (Archives of Criminology, 1974)
In Poland we have at present in towns 29 detoxication centres with 1,226 beds; people found by the police in public places in a state of intoxication are more and more often taken to detoxication centres instead of being arrested and taken into custody (a stay in a public place in the state defined as state of drunkenness is in Poland not subject to penalty). Between 1966-1972 from 60 to 70% of those arrested for drunkenness were throughout the country sent to detoxication centres and not taken into custody. The average annual number of men placed in the Warsaw detoxication centre in the years 1968-1970 amounted to approximately 27,550 and that of women to 1,500. The number of men taken to the centre for a second time during the course of a year amounted to approximately 4,200, and three or more times – 4,500; the number of women placed in a centre for the second time during the course of one year amounted to approximately 200, for the third time or more – to approximately 500. The category of individuals taken to a detoxication centre several times during the course of one year thus is substantial. There were 32% of men with a least two such stays, and 40% of women from among the total number people taken to the centre. This category of individuals is called habitual drunkenness offenders, which, as we know, exists in many countries. Selected as a sample for the studies, discussed here were not individuals who had repeatedly been taken to the detoxication centre during the course of one and the same year. The idea was to eliminate those individuals as to whom we were sure that they were alcoholics. The research, conducted in 1970 in the detoxication centre in Warsaw by the Department of Criminology of the Polish Academy of Sciences embraced that category of men who during a period of over five and a half years were at least three times taken there and the category of women who during the period of five and a half years were taken there at least twice. Each individual, listed in 1970 by the detoxication centre, in the order they were entered in the book, was checked from the beginning of 1970 in the centre’s records for the past five years (1965-1969) and in such a way material was completed on 500 men who during that period had at least been sent there three times and on 250 women sent there at least twice. Among men taken time and again to the detoxication centre there is a large percentage of older people, because in 1970 as many as 50,5% were over 40 and a mere 11.4% were below 30. The median age of these men amounted to 40.2; we find, as is known, similar figures in publications dealing with the problems of alcoholics. Those taken only three times to the centre amounted to approximately one-fourth of the total number of men, those taken 4-6 times accounted for 37%, 7-9 times – 19% and 10 or more times – 20%. Among the latter category of 98 patients of the centre 52 were taken there 10-15 times, 26 – 16-20 times and 20 – 21 times and more. As results from the above those who were only 3-6 times registered by the centre constitute 61% of the total number, and without taking into account additional data about arrests by the police of the people whose state of intoxication did not require their isolation in a detoxication centre, the true picture of the extent of deviations in the behaviour of the investigated, caused by intoxication would be distorted. That is why the decision was taken to add to the data related about the frequency of stays in the detoxication centre additional data on arrests by the police of men in a state of intoxication, who had been already registered in the centre three times, four times, six times and 8-9 times; it was not considered necessary to introduce analogical procedures for those listed many times during that period in the centre – from 10 to over 21 times, since it is to be assumed that these as a rule are already alcoholics. Taken into account in this respect was not only the period between 1965-1970, but also later years between 1971-1973, in order to find whether excessive drinking of alcohol by the investigated, causing police intervention, did not get worse. It turned out that only with men registered in the centre three times the percentage of those arrested additionally by the police did not surpass the figure of 33, but with those listed by the centre four times – it already amounted to 48%, six times – 55% and 8-9 times – 53%. This shows that beginning with 4 stays in the centre the percentage of people arrested by the police because of drunkenness already amounted to at least approximately 50%. Taking into account the number of arrests, figuring in police records, it was found that those arrested at least 5 times there, were in turn among those listed in the detoxication centre 3, 4, 6 and 8-9 times: 10%, 30%, 32% and 47%; of those listed 10 and more times: 0, 15%, 14%, and 27%. Thus the studied material is the subject of substantial differentiation if, in addition to stays in the detoxication centre, one takes into account arrests by the police and the number of such arrests. Taken into account additionally were court convictions which makes it possible to answer the question, how many men listed in the centre until the end of 1973, were neither arrested by the police nor convicted by a court for offences, as a rule committed in a state of intoxication. Of such former patients of the centre, without the behaviour patterns, referred to and connected with excessive drinking of alcohol, there remained at the end of 1973: among those listed in the centre 3 times – 44%, among those listed in the centre 4 times – 38%, among those listed in the centre 6 times – 25%, among those listed in the centre 8-9 times – 31% . Distinctly noted was an intensification of deviations in the behaviour in a state of, intoxication in the examined individuals during the course of the last three years (1971-1973). At the end of 1973 over 50% and 60% of the investigated with previous 3 and 4 stays in the centre and approximately 70% beginning with 6 stays in the centre, may without any special objections be considered alcoholics. It should, however, be borne in mind that there exists a large category of alcoholics whose systematic drinking alcohol to excess does not cause a behaviour that requires the intervention of the police and that is why, in regard even to these individuals among the investigated with whom, in addition to frequent stays in the detoxication centre, no other additional negative features were noticed, the suspicion that they may be alcoholics, is nevertheless justified. In this study under discussion here, during which no individual, psychological and medical investigations or environmental research were carried out, these problems could not be properly clarified. 82% of the men who more than once were brought to the detoxication centre were blue-collar workers and only 8.5% – white-collar workers. 63% had regular jobs and 31% worked from time to time or did not work at all (information regarding work is, however, not based on reliable data). The percentage of those who are not working (and those working from time to time) increases together with the number of stays in the centre; amounting to: 18% of those listed three times in the centre, 22% – 4-6 times, 39% – 7-9 times and 55% – 10 times and more. 50% of the men were not convicted by courts, 20% – were once convicted, 16% – 2-3 times and 14% – 4 times and more. Together with the growing frequency of being registered in the centre there also grows the percentage of those convicted by a court from 42% (3 times listed in the Centre) to 66% (in the group listed 10 times and more). 62% of the men registered in the centre as “not working” were convicted by a court, 69% – of those working from time to time and 40% – of those who were working regularly. Studying the group of men who had been convicted it was found that the late beginning of convictions, only when they were already 30 and more, is found with 31% of those convicted who are 30-39 years old and with as many as 65% among those who are 40-49; in the group with convictions when 50 and older – the first convictions occurred after 50 with all of them. Among the total with convictions only 18% were first convicted when below 21. However, among those offenders who were first convicted at the age of 17-20 we find the largest percentage (4l%) with later convictions amounting to 4 and more. Markedly smaller numbers of the men over 40 have been convicted than is the case among the younger age groups (p < 0.001). However, the percentages of recidivists, convicted 4 times and more are similar in the various age groups, beginning with the age of 30. The above-mentioned data testify above all to the fact that the majority (70%) of men listed time, and again in the detoxication centre, whose median amounted in 1970 already to 40.2 years, either had not previously been convicted at all (50%) or had faced charges only once (20%), while the category of recidivists with multiple convictions is not numerous (14%). The results of studies also testify to the fact that approximately 45% of the total number of those convicted, faced charges for the first time only when they were already 30 years old. Dealing with data on the delinquency of those convicted by a court once and 2-3 times, it was found, that in the structure of their delinquency offences against property did not surpass 22% and 23% of all the offences committed, and offences with physical or verbal aggression and other offences, as a rule also caused by insobriety, amount respectively to 68% and 60% of the committed offences. Among a small group of recidivists, convicted at least 4 times, only 45% of the recidivists committed mainly or exclusively offences against property (larcency), while in the case of 48% there dominated offences with physical and verbal aggression. To the typical offences, with physical aggression belong acts that are not particularly dangerous, such as slight bodily injury, “il-treatrnent of family members” and assaults upon policemen. Within the group referred to above only a very small sub-group of the recidivists with multiple convictions, who committed mainly aggressive acts caused by insobriety, can also found crimes in the form of more serious aggressive acts, such as robbery, serious bodily injuries, brawls, combined with the use of a dangerous instrument. Despite this, even among recidivists with severe degradation there is only an insignificant number of such recidivists who committed at least four offences combined with physical aggression ‒ there were only 7 out of 67 ‒ 10.4%; they constitute a mere 2.8% of the total of convicted persons. The group of recidivists with severe degradation and at least 4 convictions accounts for no more than 28% of the total number of those convicted; the deliquency of the remaining men who are frequently listed in the centre is rather a marginal phenomenon. During the past three years (1971-1973), side by side with the intensification of alcoholism there could be noticed among the investigated an increase in the percentage of those with convictions in the group listed 3 times in the centre from 42% to 49%, in the group listed 4 and 6 times from 44% to 57% and 62% and in the group listed 8-9 times from 53% to 62%. But the structure of the offences did not undergo any changes ‒ petty offences, that socially are less harmful and caused by insobriety, predominate. Out of the 250 women, listed at least twice in the detoxication centre during the period of 5 and a half years, have been set apart 128 women noted in police records as prostitutes (P) and 122 women about whom such data were lacking (NP). 70% of the P were listed at least 4 times (32% ‒ eight times or more). 60% of the NP were registered only twice (14% at least 8 times). The prostitutes are younger than the remaining women ‒ the age median of P arnounted to 35.4 years, that of NP ‒ 42.3 years. 48% of the women with the symbor “P” were below the age of 35 years, 24% of the NP. Among the NP as many as 30% were already 50 years old and more (among the P 13%). Those who are not prostitutes thus are considerably older, but among the prostitutes, too, are women from the age groups above 35 years. (Note that while in 1970 there were among the total number of prostitutes, known to the police throughout the whole country, 44% who were at least 31 years old, as many as 73% of the studied prostitutes registered in the Warsaw detoxication centre were at least 30 years old). Prostitutes were often arrested by the police because of drunkenness – only 30% were arrested less than 10 times, 34% from 10 to 29 times and 27% ‒ 30 times and more. Only 32% of those who were not prostitutes were arrested during this same period because of drunkenness, in the following 3 years (1971-1973) ‒ 34% and among the total of the arrested 56% were arrested only 1-2 times and a mere 22% ‒ 10 times and more. Women listed time and again in the centre have much worse data related to education and work than men, listed there from time to time. Among P there were 20% of women with incomplete primary school education, and NP ‒ 39%; 69% of the women had no trade, including P and NP; not working (or working only from time to time) were 72% of the P and 60% of the NP. Data regarding convictions testify to the fact that 64% of those who were not prostitutes had no convictions and only 6% NP were convicted by a court four and more times. Only 28% of the prostitutes had no convictions, 22% were convicted once, 20% ‒ 2-3 times, and 30%, four times and more. The first convictions at an age below 25 were found with 40% of the prostitutes and only with 11% of the NP, 31% of the P had their first conviction at the age of 30 and 7l% of the NP. Those who were not prostitutes as a rule had no convictions and among the few who had faced charges, the beginning of delinquency took place only after 30 (with approximately 30% ‒ only after 40). In the delinquency structure of P as well as NP larcency constitutes only 36% and 33%; undoubtedly this mainly means stealing from men. Most of the offences committed by P and NP are not serious. The material about women obtained from the detoxication centre points to their marked social degradation, probably reaching back to the period preceding their turning into alcoholics and also indicates the deepening of their social degradation, together with age and the intensification of their alcoholism. * The results of the research under discussion testify to the fact that the majority even of those who were registered less than 10 times during those five and a half year in the detoxication centre, are certainly already alcoholics. Studies revealed that in addition they had been frequently arrested by the police for drunkenness (though not isolated in detoxication centres) and had faced courts, charged with typical offences for people drinking alcohol to excess. Thus, even less frequent stays in a detoxication centre should already be an indication for the health and social care service to intervene, in order to find alcoholics requiring treatment.